Numerical investigation of an orogenic mesoscale convective system - Tripoli, Gregory J., author (Colorado State University. Libraries, 1986)
The interaction of topographically induced thermally and mechanically driven diurnal flow regimes in the lee of the Rockies is shown to lead to the growth of a mesoscale convection system (MCS). The results are based on a series of two-dimensional and three-dimensional nonhydrostatic numerical simulations of an intensively studied convective event based on data gathered in the 1977 SPACE (South Park Area Cumulus Experiment)/HIPLEX (High Plains Experiment). The results have been used to define six stages in the MCS genesis. The first stage, described adequately by Cotton et al. (1983), is typified by the growth of the mountain boundary layer during the morning. The second type begins as a deep convection forms in the early afternoon over the high mountain peaks. The third stage begins with the formation of an eastward propagating convective squall line system of meso- proportions in the lee wave/slope flow convergence zone 60 km east of the Continental Divide. The fourth stage occurs as the mesa- system moves eastward into a suppression zone east of the foothills and weakens. The fifth stage begins with explosive growth of the mesa- system east of the suppression zone. The final and sixth stage occurs after nightfall and is typified by the decoupling of convection from the surface and the lateral spread of meso- scale vertical motion into dispersed regions of meso- scale convection. The results demonstrate that precipitating convection is of basic importance to deepening the mountain/plains solenoid from 5 km depth for a dry circulation to tropopause depth. The persistent deep cellular circulation induces an atmospheric wind response on the scale of the Rossby Radius of Deformation (a meso-a-scale). The system core also contains a meso- scale transient circulation comprised of an internal gravity wave train. The result is the temporal oscillation of vertical motion within the core. Since convective elements (meso-y circulation) are contained primarily within the core, their intensity varies as the core meso-~ scale vertical motion oscillates. The core always exists at the western edge of the plains temperature inversion (which caps the boundary layer) until after dark. This effectively localizes the convection by preventing its horizontal spread by the emitted gravity wave motion. As a result the meso-a response can grow and the meso- core becomes long-lived. The meso- core and meso-a scale atmospheric responses move eastward with the mean tropospheric wind. Traveling internal waves emitted from the core travel at near 30 m s-1 and are inefficient in initiating convection by themselves. Most of their energy travels upward into the stratosphere during the sunlight hours. After sunset radiative effects are found to trap the meso- scale internal waves emitted by the core and force strong vertical motion at considerable lateral distances from the core. It is suggested that this may be leading to transition to popcorn convection in many observed mesoscale convective systems after sunset.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 1986.
Keywords: Weather -- Effect of mountains on; Mountain climate; Convection (Meteorology)